(untitled) (Belügyi Szemle, 2025)
Aim: Motivation is an important management tool, especially in organisations where people's skills and abilities are crucial to effective performance. An example of such an organisation is the Police, which is still people-centred despite information technology modernisation. Motivation is therefore essential not only in leadership, but also in the psychological selection process, and its components and characteristics are examined. Methodology: For each member of the law enforcement services is a must, based on the legal obligation, to have the proper health, psychic and physical condition. The psychological test can facilitate police recruit selection, which includes, among others, an Occupational Stress Questionnaire for Law Enforcement Services (OSQLES), which has been used for decades in Hungary. Findings: In according to Herzberg's two-factor theory, I review and analyse the OSQLES' relevance and suitability for law enforcement services. Value: I will answer two questions. Firstly, whether the OSQLES is a suitable method to obtain the right information through questions and scales and secondly, whether it is suitable to identify the factors of the Herzberg's theory.